2021
DOI: 10.1007/s40615-021-01062-z
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in SARS-CoV-2 Positivity by Ethnicity in Los Angeles

Abstract: Recent studies have identified notable disparities in SARS-CoV-2 infection risk among ethnic minorities. We evaluated SARS-CoV-2 test results from individuals presenting for testing in Los Angeles between June and December, 2020. We calculated prevalence ratios for various employment categories. Among 518,914 test results, of which 295,295 (56.9%) were from individuals reporting Hispanic ethnicity, SARS-CoV-2 positivity was 16.5% among Hispanic individuals compared to 5.0% among non-Hispanic individuals (p-val… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…These results are similar to a spatial study across the US which observed a greater proportion of Black individuals associated with COVID-19 and occupation was a strong predictor of cases [ 33 ]. Higher prevalence of COVID-19 were reported among Hispanic residents in Los Angeles and Orange County, potentially due to overrepresentation in industries that were considered essential during the pandemic [ 5 , 12 , 34 ]. This area of high risk observed in our study consists of minority communities who may also reside in crowded neighborhoods, may not be able to physically distance, and have other comorbidities that may worsen their COVID-19 prognosis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to a spatial study across the US which observed a greater proportion of Black individuals associated with COVID-19 and occupation was a strong predictor of cases [ 33 ]. Higher prevalence of COVID-19 were reported among Hispanic residents in Los Angeles and Orange County, potentially due to overrepresentation in industries that were considered essential during the pandemic [ 5 , 12 , 34 ]. This area of high risk observed in our study consists of minority communities who may also reside in crowded neighborhoods, may not be able to physically distance, and have other comorbidities that may worsen their COVID-19 prognosis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Each art piece that was put out for participants to view all centered upon common health promotion and disease preventing practices such as masking and distancing and are available through the Stay Connected L.A. website. 1…”
Section: Campaign Contentmentioning
confidence: 99%
“…The coronavirus disease of 2019 (COVID-19) pandemic was one such crisis that made health inequities markedly apparent. During the height of the pandemic, a study in Los Angeles of over 500,000 COVID-19 test results determined that people identifying as Hispanic tested positive for COVID-19 at rates over three times higher than people who did not identify as Hispanic (1). Further, Hispanics in Los Angeles had a COVID-19 mortality rate of 192 per 100,000 persons, compared to 119 for non-Hispanic Black individuals and 69 for non-Hispanic White individuals, respectively (2).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, lack of paid sick leave and protections for missed work, as well as being required to work despite illness and living in crowded housing, have prevented some workers from quarantining when exposed or isolating when infected [ 4 , 6 - 8 ]. Because many essential jobs are held by racial and ethnic minority workers, mortality and morbidity both directly and indirectly related to COVID-19 have disproportionately affected these population segments [ 3 , 9 - 12 ] and are likely reflected in national statistics for COVID-19 by race and ethnicity. For example, Hispanic or Latino persons were 1.5 times as likely to be a COVID-19 case, 2.2 times as likely to be hospitalized, and 1.8 times as likely to die, compared to non-Hispanic whites [ 13 ].…”
Section: Introductionmentioning
confidence: 99%